Recalculation of minimum wave heights from coastal boulder deposits in the Bristol Channel and Severn Estuary, UK: implications for understanding the high-magnitude flood event of AD 1607 - Haslett, Simon K.; Wong, Bernardine R. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2021)
A high-magnitude coastal flood event catastrophically affected the macrotidal Bristol Channel and Severn Estuary in southwest Great Britain, United Kingdom, on 30th January 1607 causing an estimated 2000 fatalities. Historical and physical evidence has provided a basis for the development of a theory that the flood may have been due to a tsunami rather than a storm. Previous studies have collected field data to test this hypothesis including a dataset of 136 wave-transported boulder clasts that was utilised to estimate minimum wave heights through hydrodynamic equations in 2007, but the dataset has hitherto remained unpublished in full. Since 2007 these equations have undergone refinement and for this paper minimum wave heights were recalculated from boulder measurements using revised hydrodynamic equations and presents the complete dataset for the first time. A recent study claiming that such equations are flawed is considered premature, given ongoing refinements to the equations. The results of the present study indicate that a tsunami 4.2 m high can explain the dislodgement of all boulders measured, equivalent to a storm wave height of 16.9 m, which is considerably greater than observed storm wave heights in the region. An up-channel increase in minimum wave height is also suggested by these data, generally corroborating the 2007 study, which may be due to wave amplification caused by the overall funnel-shape of the embayment. The areas worst affected by the 1607 flood are located in the coastal lowlands of the inner Bristol Channel and Severn Estuary, coinciding with the highest minimum estimated wave heights.